Interceptive Orthodontic Strategy for Children with Cleft Lip and Palate: A Scoping Review of Appliances and Intervention Timing - Suci Oktavani Ritonga; Iwan Ahmad Musnamirwan (Journal of Social Research, 2026)
Cleft lip and/or palate (CLP) is a craniofacial congenital disorder causing upper jaw growth disorders, malocclusion, and functional/aesthetic impairments during childhood. Interceptive orthodontic strategies in children with cleft lip and palate: a scoping review of the tool and the timing of the intervention guide early dentofacial growth, yet tool types and timing vary widely, necessitating evidence mapping for clinical practice. This scoping review followed the PRISMA-ScR framework, searching PubMed and Scopus (2015–2025) for primary studies on interventional orthodontics in children with CLP. From 452 articles identified, 10 were included after screening and synthesis. Tools included presurgical nasoalveolar molding (PNAM), rapid maxillary expansion (RME), facemasks, and bone-anchored maxillary protraction (BAMP). Interventions ranged from neonatal to adolescent phases. BAMP yielded superior sagittal skeletal and facial profile corrections, especially pre-pubertal peak. Passive devices like NAM enhanced soft tissue repair and preoperative nasolabial symmetry. Interceptive orthodontics in CLP depends on device selection and timing; anchorage-based options like BAMP excel in active growth, while NAM suits presurgical aesthetics. These findings inform clinical decisions and future research in CLP orthodontic management.